Students' social presence in online learning system - Jamil, Nur Jannah (2014)
The purposes of this study are to identify students' perceptions on social presence on online learning and to investigate students' social presence in online learning. Next, this study will also identify students' social presence in online learning in relation to their academic performance. The respondents for this study will be 33 undergraduate students who enrolled in Authoring Language course. One of the most highlighted issues in online learning is interaction process that takes place between either learners and learners or learners and teacher. As mentioned by Badrinathan and Gole [1], online learning requires the teacher or the instructor to be responsible in ensuring that the learners interact with one another. The interaction will encourage the students to voice out their thoughts and respond towards others' idea through computer mediated communication (CMC). Given that social presence is likely related to feeling rather than reason [2], the sense of connectedness among learners would stimulate them to become more interactive in online learning. Hence, rather than trying to acquire the knowledge individually, learners would have much experience in sharing and cooperating with their peers in the whole process of learning. Furthermore, social presence is considered as one of the keys to the success of online learning [3] when it has great influence in online interaction, user satisfaction, depth of online discussions, online language learning and critical thinking [4]. This study will be implementing quantitative approach with triangulation of data from questionnaire and students' online transcript. Quantitative data from questionnaires will be analyzed using SPSS (Statistical Package for the Social Science). As for the online transcript, the data will be analyzed through content analysis technique. With the findings of this study, it is hoped that students, teachers or instructors and the administrations of higher educational institutions will be more aware towards the importance of social presence in inculcating effective learning process via online system.